Zika Virus Vaccines: Challenges and Perspectives - das Neves Almeida, Raquel (Vaccines (Basel), 2018)
Zika virus is an arbovirus that has rapidly spread within the Americas since 2014, presenting a variety of clinical manifestations and neurological complications resulting in congenital malformation, microcephaly, and possibly, in male infertility. These significant clinical manifestations have led investigators to develop several candidate vaccines specific to Zika virus. In this review we describe relevant targets for the development of vaccines specific for Zika virus, the development status of various vaccine candidates and their different platforms, as well as their clinical progression.